The success of ornamental coral propagation in Banyuwangi East Java, Indonesia: observation of different depths and species - Johan, Ofri; Ginanjar, Rendy; Budiyanto, Agus; Ardi, Idil; Priyadi, Agus; Kunzmann, Andreas (Frontiers in Marine Science, 2023)
Ornamental corals have become the main attention objects for many hobbyists and have already become a source for foreign exchange in developing countries. Through ornamental coral propagation, the continuity of ornamental coral trade can be guaranteed and the level of damage is very limited. The propagation technique has been developed by ornamental coral exporters in several locations in Indonesia. This paper has two main objectives: a) to determine the site suitability of ornamental coral propagation locations and b) to provide a detailed description of the development and progress of ornamental coral propagation in Indonesia with first-hand information from 14 companies. The present study showed that the highest growth rate was found on branched specimens of E. glabrescens (2.50 cm) after 5 months, and the lowest growth rate was found on branched specimens of E. paraancora (0.42 cm). Corals with larger branches or with two or three branches of E. glabrescens and E. paraancora have a low mortality and increased the number of branches to three to four branches after 5 months. Small colonies also survive with a mortality of 20%. The cultured corals can grow optimally and have exotic colors when placed at different depths. Best coral growth was obtained from fast-growing coral species at a shallow depth (<10 m). While medium depth (10–15 m) was suitable for corals with moderate growth rates, the deeper depths (> 15 m) were characterized by bright-colored corals with slow-growing rates. Color quality and growth of corals are closely related to some supporting factors such as the suitability of locations that have different physical, biological, and chemical factors in different depths and thus follow different requirements among coral species. Location choices determine the success of coral cultivation both for ornamental and restoration purposes. These results are valuable background information for traded ornamental corals that can be utilized by propagators.